Antitumor effects of polysaccharides from Tetrastigma hemsleyanum Diels et Gilg via regulation of intestinal flora and enhancing immunomodulatory effects in vivo - Zhou, Fangmei; Lu, Yan; Sun, Tong; Sun, Ling; Wang, Bixu; Lu, Jingjing; Li, Zhimin; Zhu, Bingqi; Huang, Shigao; Ding, Zhishan (Frontiers in Immunology, 2022)
Tetrastigma Hemsleyanum Diels et Gilg is a traditional Chinese herbal medicine with high medicinal value, which included biological activities including anti-tumor, antioxidant and anti-inflammatory. However, several studies focus on flavonoids in Tetrastigma Hemsleyanum tubers, with few studies on the enhanced immune effect of Tetrastigma Hemsleyanum polysaccharides (THP). In this study, we evaluated the antitumor effect of THP in lung tumor model and explore the mechanism of antitumor activity through intestinal flora. Besides, the cyclophosphamide (CTX)-induced immunosuppression model was to declare the immunomodulatory effect of THP in the immunosuppressive state induced by anti-tumor drugs. The results showed that THP increased the content of ileum secreted immunoglobulin A (SIgA) and cecum short-chain fatty acid (SCFAs), and improved microbial community diversity, regulating the relative abundance of dominant microbiota flora from phylum level to genus level, and recovering the intestinal microflora disorder caused by tumors. Also, THP can increase liver, thymus, and spleen index and improve immune organ atrophy in CTX-treated mice. THP can up-regulate routine blood counts (hemoglobin (HGB), white blood cell (WBC), red blood cell (RBC), platelet (PLT), lymphocyte (LYMPH) and Neutrophil (NEUT)) and stimulate the production of serum cytokines Interferon-γ (IFN-γ), interleukin-10 (IL-10), interleukin-12 (IL-12), interleukin-6 (IL-6), tumor necrosis factor (TNF-α) and monocyte chemoattractant protein-1 (MCP-1). THP also promoted macrophage phagocytic index, NK cell activation, complement, and immunoglobulin (IgG, IgA, IgM) levels. The detection of Splenic lymphocyte proliferation and T lymphocyte subsets also sideways reflects that THP can restore CTX-induced immune inhibition in mice. In conclusion, this study suggests that THP can effectively achieve the enhanced anti-tumor effect, regulate gut microbiota and improve the immunosuppression induced by anti-tumor drugs. Therefore, THP can enhance the immune capacity and provide novel immunomodulatory and anti-neoplastic adjuvant agents.